MICROBIOLOGICAL RISK ASSESSMENT OF FISHERY PRODUCT IN INDONESIA: A PROPOSED MODEL FOR THE RISK OF Vibrio parahaemolyticus IN SHRIMP - Novalia Rachmawati; Radestya Triwibowo (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2012)
Increasing fish consumption value should be supported by enhancing the safety and quality offish products. Microbiological level is most of importance since every food contains microorganismswhich could multiplicate due to temperature abuse and time delay during handling and processing.Risk assessment is a structurally and scientifically based approach aimed to protect consumerfrom risk (hazard) particularly microbiological hazard when consuming certain food. Microbiologicalrisk assessment of fishery products have not been structurally developed in Indonesia, eventhoughseveral initial data on hazard identification have been available. As an attempt to build an integratedrisk assessment, a model for microbiological risk of pathogenic  Vibrio parahaemolyticus inshrimp will be proposed in this article. The available data could be used as a starting point whileother required data could be collected in collaboration with other related institutions.